Contribution of oxygen related defects to the electronic transport in SnO2 sol-gel films - Scalvi, Luis Vicente de Andrade [UNESP]; Geraldo, V.; Messias, F. R.; Li, M. S.; Santilli, C. V. [UNESP]; Pulcinelli, S. H. [UNESP] (Taylor & Francis, 2001)
SnO2 deposited by sol-gel is a polycrystalline film with small grain size. Oxygen present at a less grain boundary traps electrons and then the depletion layer around the potential barrier of the grain boundary becomes wider, comparable to the grain size. We have modeled the conductivity taking into account the trapped charge at the depletion layer of the grain boundary and other scattering mechanisms such as ionized impurity and polar optical. Experimental data of photoconductivity of SnO2 sol-gel films are simulated considering the dominant scattering at grain boundary and crystallite bulk. The fraction of trapped charge at the grain boundary depends on temperature and wavelength of irradiating light, being as high as 50% for illumination in the range 500-600 nm for SnO2-2%Nb as grown sample annealed in air to 550°C. This fraction can be quite reduced depending on exposure to light and annealing under different oxygen partial pressure conditions.
Keywords: Oxygen; Photoconductivity; Sol-gel; Tin dioxide